A new species of nine-spined stickleback, Pungitius modestus (Gasterosteiformes, Gasterosteidae), from northern Honshu, Japan - Matsumoto, Tatsuya; Matsuura, Keiichi; Hanzawa, Naoto (Zootaxa, 2021)
A new species of nine-spined stickleback, Pungitius modestus, is described based on the holotype and 17 paratypes (38.7–51.7 mm standard length) collected from the inland area of Yamagata Prefecture, northern Honshu, Japan. The new species is distinguished from the other species of Pungitius by the following combination of characters: 30–32 small unconnected lateral plates; dorsal-fin rays VIII–X (usually IX)+9–11; anal-fin rays 7–10 (usually 8); pectoral-fin rays 10; a short spiny dorsal fin base (26.5%–29.8% SL); the first spiny dorsal fin spine behind the pectoral-fin base; a long pre-anal fin (59.9%–67.4% SL); the anal-fin spine below the 1st–3rd dorsal-fin rays; a short pelvic-fin spine (6.3%–9.1% SL); a short anal-fin spine (4.1%–6.0% SL); a long caudal peduncle (14.3%–19.7% SL); no body markings; membranes of the dorsal-fin spines dark brown with black pigments; the entire male body, and soft dorsal and anal fins, becoming black in the breeding season; the anteroventral process of the ectocoracoid present; and the dorsal extension of the ascending process of the pelvis level with the dorsal-most actinost.